Alternative splicing of EZH2 regulated by SNRPB mediates hepatocellular carcinoma progression via BMP2 signaling pathway - Xingyu Wang; Weiyi Liu; Chunai Zhan; Yuanyuan Zhang; Xinyu Li; Yaoyun Wang; Mengfei Sheng; Madiha Maqsood; Hang Shen; Anmin Liang; Wei Shao (iScience)
Summary: Increasing evidence suggests that aberrant alternative splicing plays crucial roles in tumorigenesis. However, the function of EZH2 splice variants as well as the mechanism by which EZH2 alternative splicing occurs in hepatocellular carcinoma (HCC) remain elusive. Here, we analyzed both our own and published transcriptomic data, obtaining 19 splice variants of EZH2 in addition to canonical full-length EZH2-A in HCC. We found that expression of EZH2-A/EZH2-B in tumor tissues and cell lines was significantly higher than in normal tissues. Conversely, EZH2-C expression was lower in tumor tissues and cell lines than in normal tissues. Further functional analysis indicated that unlike full-length EZH2-A that promotes H3K27 methylation, EZH2-C reduced H3K27me3 levels. EZH2-C inhibited proliferation, migration, invasion of HCC cells. Moreover, EZH2-A and EZH2-C regulate the BMP2 signaling pathway oppositely. Mechanistically, EZH2’s alternative splicing was mediated by splicing factor SNRPB. In summary, this study revealed that alternative splicing of EZH2 regulates HCC.